Solubilization of Hydroxypropyl-β-Cyclodextrin on Cholesterol in Aqueous Solution - Zou, Changjun; Zhou, Lu; Wang, Yali; Li, Lu (Journal of Applied Solution Chemistry and Modeling, 2014)
Hydroxypropyl-β-Cyclodextrin (HP-β-CD), prepared via reaction of β-Cyclodextrin (β-CD) and propylene oxide (PO), is utilized to research solubilization of HP-Î²-CD on cholesterol in aqueous solution. HP-β-CD is characterized by Fourier Transform Infrared Spectrometry (FT-IR), and concentrations of cholesterol solution are measured by ultraviolet and visible (UV VIS) spectrophotometer. The research on optimal synthesis conditions of HP-β-CD indicates that sodium hydroxide amounts have the most effect on yields of product. The maximum solubilization multiples of HP-β-CD reaches 15, below which molecular rate of HP-β-CD and cholesterol in inclusion complex is 1:1.